Habitats and Biota of the Gulf of Mexico: Before the Deepwater Horizon Oil Spill: Volume 2: Fish Resources, Fisheries, Sea Turtles, Avian Resources, Marine Mammals, Diseases and Mortalities - Herb Ward, C. (Springer Nature, 2017)
environmental management; marine; freshwater sciences